Efeito antinociceptivo do extrato aquoso das folhas de Passiflora cincinnata Mast. (Passifloraceae) em camundongos - Lavor, Érica Martins de (2022)
The species Passiflora cincinnata Mast. it is native to the Caatinga biome, whose use is described in traditional medicine for analgesic and anti-inflammatory purposes. However, few studies that prove its use are described in the literature. Thus, this work aims to evaluate the antinociceptive activity of P. cincinnata aqueous leaf extract (Pc-Aq) through preclinical assays in mice. The pharmacognostic characterization of the plant drug was performed, and the chemical composition of the aqueous extract (Pc-Aq) was evaluate by high-performance liquid chromatography coupled to a diode array detector (HPLC-DAD). The antinociceptive evaluation of the extract administered orally, at doses of 100 and 200 mg/kg was performed using in vivo chemical models (acetic acid-induced abdominal constriction and formalin-induced paw licking test) and thermal (hot plate test) of nociception. The mechanism of action was evaluated with opioid receptor antagonist drugs, potassium channels, TRPV-1, muscarinic, serotonergic (5-HT3) and α-2 adrenergic. The rota-rod test was performed to verify the possible interference of the treatment with the extract in the animal’s motor performance. The results of chemical analyzes indicated the presence of the flavonoids vitexin and isoorientin in Pc-Aq. Treatment with the extract reduced the number of abdominal contortions and decreased paw licking time in both phases of the formalin test (p < 0.05). In the hot plate test, the extract increased the latency time for paw withdrawal, indicating a reduction in painful behavior. The evaluation of the antinociceptive mechanism indicated a possible action of central pathways in the antinociceptive activity, with participation of opioid receptors with influence of potassium channels and α-2 adrenergic pathway, without significant change in motor control, assessed by the rota-rod test. Therefore, this study suggests that Pc-Aq has an antinociceptive action mediated by central pathways, whose action can be attribute to the presence of flavonoids present in the extract.